Recipient TIM4 signaling regulates ischemia reperfusion-induced ER stress and metabolic responses in liver transplantation: from mouse-to-human - Hirao, Hirofumi; Kageyama, Shoichi; Nakamura, Kojiro; Kadono, Kentaro; Kojima, Hidenobu; Siyuan, Yao; Farmer, Douglas G.; Kaldas, Fady M.; Dery, Kenneth J.; Kupiec-Weglinski, Jerzy W. (Frontiers in Transplantation, 2023)
T-cell immunoglobulin and mucin (Tim)4 is expressed on APCs, including macrophages, as one of the main amplifiers in the mechanism of liver ischemia-reperfusion injury (IRI) following orthotopic liver transplantation (OLT). Though donor Tim4 selectively expressed on Kupffer cells serves as a checkpoint regulator of innate immune-driven IRI cascades, its role on cells outside the OLT remains unclear. To dissect the role of donor vs. recipient-specific Tim4 signaling in IR-induced stress and hepatocellular function, we employed a murine OLT model utilizing Tim4-knockout (KO) mice as either donor or recipient (WT→WT, WT→Tim4-KO, Tim4-KO→WT). In the experimental arm, disruption of donor Tim4 attenuated IRI-OLT damage, while recipient Tim4-null mutation aggravated hepatic IRI concomitant with disturbed lipid metabolism, enhanced endoplasmic reticulum stress, and activated pro-apoptotic signaling in the grafts. In the in vitro study, murine hepatocytes co-cultured with Tim4-null adipose tissue showed enhanced C/EBP homologous protein (CHOP) expression pattern and susceptibility to hepatocellular death accompanied by activated caspase cascade in response to TNF-α stimulation. In the clinical arm, liver grafts from forty-one transplant patients with enhanced TIM4 expression showed higher body mass index, augmented hepatic endoplasmic reticulum stress, enhanced pro-apoptotic markers, upregulated innate/adaptive immune responses, exacerbated hepatocellular damage, and inferior graft survival. In conclusion, although TIM4 is considered a principal villain in peri-transplant early tissue injury, recipient TIM4 signaling may serve as a savior of IR-triggered metabolic stress in mouse and human OLT recipients.